Hormonal Contraception and Bone Health in Adolescents - Bachrach, Laura K. (Frontiers in Endocrinology, 2020)
Hormonal contraception is prescribed commonly to adolescents for myriad indications from pregnancy prevention to treatment for hirsutism or irregular, heavy menses. Although use of these hormones generally has no effect or benefits bone health in mature premenopausal women, the same may not be true for adolescents. The teens years are a critical period for acquiring peak bone strength. Sex hormones, growth hormone and insulin-like growth factors (IGFs) interact to modulate changes in bone size, geometry, mineral content and microarchitecture that determine skeletal strength. Combined oral contraceptives (COCs) and intramuscular depo medroxyprogesterone (DMPA) can compromise the expected gains in adolescence by altering estrogen and IGF concentrations. Use of these medications have been associated with slower accrual of bone mineral density (BMD) and increased fracture risk in some studies. This review takes a critical look at limitations of current knowledge of COCs, DMPA and the newer forms of long-acting reversible contraceptive methods.